Madagascar: open-source software project for multidimensional data analysis and reproducible computational experiments. (21st November 2013) - Fomel, Sergey; Sava, Paul; Vlad, Ioan; Liu, Yang; Bashkardin, Vladimir
The Madagascar software package is designed for analysis of large-scale multidimensional data, such as those occurring in exploration geophysics. Madagascar provides a framework for reproducible research. By "reproducible research" we refer to the discipline of attaching software codes and data to computational results reported in publications. The package contains a collection of (a) computational modules, (b) data-processing scripts, and (c) research papers. Madagascar is distributed on SourceForge under a GPL v2 licensehttps://sourceforge.net/projects/rsf/ . By October 2013, more than 70 people from different organizations around the world have contributed to the project, with increasing year-to-year activity. The Madagascar website ishttp://www.ahay.org/